Chk1 Inhibition Hinders the Restoration of H3.1K56 and H3.3K56 Acetylation and Reprograms Gene Transcription After DNA Damage Repair - Ding, Nan; Shao, Zhiang; Yuan, Fangyun; Qu, Pei; Li, Ping; Lu, Dong; Wang, Jufang; Zhu, Qianzheng (Frontiers in Oncology, 2022)
H3K56 acetylation (H3K56Ac) was reported to play a critical role in chromatin assembly thus participates the regulation of DNA replication, cell cycle progression, DNA repair, and transcriptional activation. To investigate the influence of DNA damage regulator on acetylation of histone H3 and gene transcription, U2OS cells expressing SNAP-labeled H3.1 or SNAP-labeled H3.3 were treated with ATM, ATR, or Chk1 inhibitor after ultraviolet (UV) radiation. Levels of H3.1K56ac, H3.3K56ac and other H3 site-specific acetylation were checked at different time points until 24 hours after UV radiation. The difference of gene transcription levels was also examined by mRNA sequencing. The results identified Chk1 as an important histone H3K56 acetylation regulator of the restoration of both H3.1K56ac and H3.3K56ac. Moreover, Compromising Chk1 activity via chemical inhibitors suppresses gene transcription after UV radiation. The study suggests a previous unknown role of Chk1 in regulating H3K56 and some other site-specific H3 acetylation and in re-programing the gene transcription during DNA damage repair.